PENGARUH MODAL KERJA, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TEDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2020 - Syaranamual, Irelda Sari; Widiarti, Dian (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The The purpose of the study was to determine and analyze the effect of working capital (WCT), liquidity (CR), and firm size (Firm Size) variables on profitability in consumer goods industrial sector companies for the 2016-2020 period. The population in this study is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. The sampling technique was carried out by purposive sampling method and obtained 21 companies in the consumer goods industry sector. The data used is secondary data in the form of financial reports (Annual Report). The data analysis method in this study used multiple linear regression analysis. Based on the results of the partial analysis (t-Test) shows that the working capital variable has a negative and significant effect on profitability, liquidity has a positive and not significant effect on profitability and company size has a negative and significant effect on profitability. Meanwhile, the results of the simultaneous analysis (f-Test) show that working capital, liquidity, and company size have a positive and significant effect on profitability in consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period.